Reflections of Chinese Middle School English Instructors and Learners on Efficiency of English Education - Wu, Yiqiang; Fu, Ping; Hall, Timothy (Advances in Social Sciences Research Journal, 2024)
This article sheds light on a survey study on the reflection of English teaching and learning by teachers and students in high schools in China. Forty-Two English teachers and 156 students from four high schools in Hunan Province participated in the study. They responded to questions through an online survey about their English learning and teaching experience. The survey also asked the participants to share their comments and opinions on how to make improvement and changes to make English education more effective and efficient. The data were discussed and analyzed in comparing with English learning experience and process of native speakers of English in the United States. Findings of this study suggest that more exposure to authentic English, extensive reading, and daily oral communication be enhanced to improve the learners’ proficiency. This study indicates that the current learning process and instructional sequence are not effective and efficient. Some fundamental issues related to learning sequence, learning efficiency, curriculum policy and design are addressed, and suggestions are made for future research and English education reform.